Pengaruh Pendidikan Terhadap Tingkat Kemiskinan Dan Pengangguran Di Provinsi Aceh - Adela; Andiny, Puti; Asnidar (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2024)
This research aims to investigate the influence of education on poverty and unemployment in Aceh within the timeframe of 2013-2022. The method employed is time series data analysis using path analysis. The results indicate that education has a direct, negative, and significant impact on the poverty rate, as well as a direct, negative, and significant impact on the unemployment rate. Additionally, it is found that poverty has a direct, positive impact on unemployment, albeit not significant. Indirectly, education also exerts a significant influence on the unemployment rate through the poverty variable. The total coefficient of determination in thus study is 99,44%, while the remaining 0,03% is influenced by other variables such as per capita income, labor force participation rate, and others.